Clinical Impact and Cellular Mechanisms of Iron Overload-Associated Bone Loss - Jeney, Viktória (Frontiers in Pharmacology, 2017)
Diseases/conditions with diverse etiology, such as hemoglobinopathies, hereditary hemochromatosis and menopause, could lead to chronic iron accumulation. This condition is frequently associated with a bone phenotype; characterized by low bone mass, osteoporosis/osteopenia, altered microarchitecture and biomechanics, and increased incidence of fractures. Osteoporotic bone phenotype constitutes a major complication in patients with iron overload. The purpose of this review is to summarize what we have learnt about iron overload-associated bone loss from clinical studies and animal models. Bone is a metabolically active tissue that undergoes continuous remodeling with the involvement of osteoclasts that resorb mineralized bone, and osteoblasts that form new bone. Growing evidence suggests that both increased bone resorption and decreased bone formation are involved in the pathological bone-loss in iron overload conditions. We will discuss the cellular and molecular mechanisms that are involved in this detrimental process. Fuller understanding of this complex mechanism may lead to the development of improved therapeutics meant to interrupt the pathologic effects of excess iron on bone.